On the wiener's attack into lucas based El-gamal cryptosystem in the elliptic curve over finite field - Wong, Tze Jin; Koo, Lee Feng; Yiu, Pang Hung (International Journal of Science and Engineering Investigations, 2018)
This paper reports a security analysis on the Lucas Based El-Gamal Cryptosystem in the Elliptic Curve Over Finite Field.Wiener’s Attack was selected to analyzethe cryptosystemunder a bad implementation practice. Result showed that the cryptosystem wasweak if the chosen keys were too small among those inthe order of group G.